A phenomenological investigation of the impact of study abroad experiences on the development of intercultural communication skills in college students - Harmanda, Dea; Sujadi, Eko; Yandri, Hengki (Empathy : Jurnal Fakultas Psikologi, 2024)
Intercultural communication represents a significant challenge in the adaptation process for students studying outside their home regions. This study aims to examine the impact of studying abroad on the development of students' intercultural communication skills. A qualitative approach, utilizing a case study design, was employed for this research. The study involved four students who were currently studying abroad, selected through purposive sampling. Semi-structured interviews were conducted to gather insights from each participant. The analysis revealed four key themes: personality resilience, communication skills, psychological adaptation, and cultural awareness. The findings suggest that psychological resilience plays a crucial role in facilitating effective intercultural communication. Additionally, interpersonal communication skills are essential in this process. A common psychological challenge faced by students is homesickness, which can be mitigated by maintaining regular communication with family members. Studying abroad also enhances students' awareness of Indonesia's cultural diversity, prompting them to expand their understanding of different cultures, values, environments, and norms. This study underscores the importance of strengthening guidance and counseling services in higher education to support students' adaptation to new environments.